Jig for pouring plastic pulley - CAO QIUHUA (2022)
The utility model discloses a plastic pulley pouring jig which comprises an upper cover, a lower bottom, an ejection block and an ejection air cylinder, the lower bottom is connected with the ejection air cylinder, the upper cover is arranged on the top of the lower bottom and matched with the lower bottom to form a forming cavity used for forming a product, and the ejection block is arranged on a piston rod of the ejection air cylinder and can move up and down in the forming cavity. And the upper cover and the lower bottom are both made of metal materials. The upper cover and the lower bottom are both made of metal materials, the phenomenon that the jig deforms during high-temperature machining is effectively avoided, and therefore the roundness and precision of product production are guaranteed, meanwhile, after machining is completed, the ejection air cylinder drives the ejection block to move upwards, the ejection block ejects the product upwards from the interior of the forming cavity to be demoulded, an